Starship troopers 2 hero of the federation - Tippett, Phil; Neumeier, Edward (Columbia TriStar Home Entertainment ; distributed in the Philippines by MagnaVision, 2003)
A group of Starship Troopers hide in an abandoned outpost after battling alien bugs. The group recovers, but fails to realize that more danger is ahead.